The study of some nuclear properties of even-even114-120Cd isotopes using interacting boson model-1 - Nasef , Dalenda M.; Bogrin , Suad M.; Eshaftri , Najat S.; Zwam , Ayad E.; El-kadi, Sadiq M. (Journal of Pure & Applied Sciences, 2021)
Nuclear properties of even-even 114-120Cd are studied in the framework of the interacting boson model (IBM-1). In this study, we have determined the most appropriate Hamiltonian for the study of even-even Cd (114-120) to calculate, its energy levels. The values of parameters have been determined using the (IBM1) Hamiltonian which yield the best fit to the available experimental energy levels. In addition, the backbending (moment of inertia as a function of (ħω)) of the energy levels for each isotope was indicated through the experimental and calculated values of the energy levels. A simulation program with MATLAP-18 has been built to obtain the theoretical energy levels for Cadmium isotopes with neutron number N=16, 18, 20 and 22 up to spin-parity 〖14〗_1^+,〖14〗_1^+,〖14〗_1^+,〖and16〗_1^+, respectively. The ratio of excitation energies of the first 4+ and the first 2+ excited states, R4/2 is also studied for the classification of symmetry of the nuclei. The results show that the 114-120Cd isotopes are γ – unstable rotor nuclei and they are dynamical symmetry O(6).